2017
DOI: 10.7196/samj.2017.v108i1.12548
|View full text |Cite
|
Sign up to set email alerts
|

Good correlation between the Afinion AS100 analyser and the ABX Pentra 400 analyser for the measurement of glycosylated haemoglobin and lipid levels in older adults in Durban, South Africa

Abstract: This study supports the use of the Afinion AS100 analyser in POC testing for the measurement of HbA1c, triglycerides and HDL-C in a South African setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…[5] In both these studies, no follow-up of patients was performed to assess the effects of POCT on diabetes control at a later stage. [5,15] Our study showed good correlation between the Quo-Test POCT HbA1c values and NHLS laboratory values. Pillay et al [1] showed that the majority of patients with diabetes are diagnosed and have their therapy initiated at their local healthcare clinic.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…[5] In both these studies, no follow-up of patients was performed to assess the effects of POCT on diabetes control at a later stage. [5,15] Our study showed good correlation between the Quo-Test POCT HbA1c values and NHLS laboratory values. Pillay et al [1] showed that the majority of patients with diabetes are diagnosed and have their therapy initiated at their local healthcare clinic.…”
Section: Discussionmentioning
confidence: 52%
“…Recently, Abbai et al [15] demonstrated in their study in Durban, SA, that there was good correlation between POCT and laboratory HbA1c values using the Afinion AS100 point-of-care analyser. This study, however, only included patients aged >50 years (mean 66 years).…”
Section: Discussionmentioning
confidence: 98%
“…One drop of blood will be taken up by the test strip and read by the machine. Good correspondence exists between the Alere point-of-care (PAC) analyser results and reference laboratory tests for HbA1c and lipid levels [171, 172]. Following Rodondi et al [173], the following clinically relevant cut-off values should be considered for total cholesterol (≥ 5.6 mmol/l), HDL-C (≤ 1.41 mmol/l), and LDL-C (≥ 3.40 mmol/l).…”
Section: Methodsmentioning
confidence: 99%
“…Fourthly, precision studies: precision performance forms the cornerstone for the assessment of clinical utility of a test or an instrument. Abbai et al [1] have not presented data with regard to imprecision performance of the POC analyser for the tests evaluated. Shephard et al [5] have proposed desirable imprecision goals for POC devices for HbA1c (coefficient of variation 3%) and lipid parameters.…”
mentioning
confidence: 99%
“…The American Diabetes Association also provide recommendations for HbA1c precision. Abbai et al [1] only evaluated performance of Afinion HbA1c with regard to correct categorisation of patients at one medical decision point (HbA1c 6.5%). As one of the primary roles of POC testing (POCT) is the monitoring of diabetic patients receiving treatment in order to allow for a more prompt change in management, evaluation at other important medical decision limits, e.g.…”
mentioning
confidence: 99%